Penanganan Sengketa Ekonomi Syariah Perspektif Cita Hukum di Pengadilan Tinggi Agama Semarang - Mohammad Jamaludin Jamaludin (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2020)
This article examines the handling of sharia economic disputes from the perspective of the ideals of law in the Religion High Court of Semarang, considering that up to now many decisions of the Religious High Court have been pursued at the cassation level (Supreme Court). The focus of this research study is to answer a number of issues, namely: how is the mechanism for handling sharia economic disputes in the Religion High Court of Semarang, what is the legal basis used by judges in the process of examining sharia economic disputes, and how the review of legal ideals towards handling sharia economic disputes in the Religion High Court of Semarang. Judging from the type, this article was categorized as field research with an empirical juridical approach. In analyzed the data, the writer used descriptive-analytical methods, by described primary data that the author has obtained in the Religion High Court of Semarang, supplemented with secondary data related to handling sharia economic disputes in the Religion High Court, then analyzed using the legal ideal theory which includes justice, legal certainty, and expediency. Based on the results of the research conducted by the writer in the Religion High Court of Semarang, the writer can conclude that, the handling of sharia economic disputes in the Religion High Court of Semarang has not been fully implemented as it should. The handling of sharia economic disputes in the Religion High Court of Semarang is carried out by examining and adjudicate cases based on facts / sitting cases contained in the appeal case file sent by the religious court that has examined and decided the case at the first level, plus an additional examination if the judge consider there are things that require clarity or to add to the completeness of evidence. A review of the legal ideals for handling sharia economic disputes in the Religion High Court of Semarang include: in terms of the ideals of the law of justice, judges in realizing the ideals of the law of justice are still constrained by vague provisions in the laws and regulations in which regulate about the procedures for examining sharia economic disputes in the level of appeal, which makes the judge unable to realize the desired justice. Judging from the ideals of legal certainty, the obstacle in realizing this legal ideal is the absence of special provisions regulate about civil procedural law (procedures for examining cases), especially sharia economic disputes at the appellate court, additionally there are several Supreme Court jurisprudences that are conflicting/contradicting. While in terms of the legal ideal of expediency, some have fulfilled this legal ideal because it is in accordance with the provisions that regulate the costs of handling cases and the duration of handling cases. Artikel ini mengkaji tentang penanganan sengketa ekonomi syariah perspektif cita hukum di Pengadilan Tinggi Agama Semarang, mengingat hingga saat ini banyak putusan Pengadilan Tinggi Agama diupayakan hukum di tingkat kasasi. Fokus kajian penelitian ini adalah untuk menjawab beberapa persoalan, yaitu: bagaimana mekanisme penanganan sengketa ekonomi syariah di Pengadilan Tinggi Agama Semarang, apa dasar hukum yang digunakan hakim dalam proses pemeriksaan sengketa ekonomi syariah, dan bagaimana tinjauan cita hukum terhadap penanganan sengketa ekonomi syariah di Pengadilan Tinggi Agama Semarang..Dilihat dari jenisnya, artikel ini dikategorikan sebagai penelitian lapangan (field research) dengan pendekatan yuridis empiris. Dalam menganalisis data, penulis menggunakan metode deskriptif-analitis, yaitu dengan menggambarkan data primer yang telah penulis dapatkan di Pengadilan Tinggi Agama Semarang, dilengkapi dengan data sekunder terkait penanganan sengketa ekonomi syariah di Pengadilann Tinggi Agama, selanjutnya dianalisis menggunakan teori cita hukum yang meliputi keadilan, kepastian hukum, dan kemanfaatan.Berdasarkan hasil penelitian yang penulis lakukan di Pengadilan Tinggi Agama Semarang, penulis dapat menyimpulkan bahwa, penanganan sengketa ekonomi syariah di Pengadilan Tinggi Agama Semarang belum sepenuhnya berjalan sebagaimana mestinya. Penganganan sengketa ekonomi syariah di Pengadilan Tinggi Agama Semarang dilaksanakan dengan cara memeriksa dan mengadili perkara secara ulang berdasarkan fakta/duduk perkara yang terdapat dalam berkas perkara banding yang dikirimkan oleh pengadilan agama yang telah memeriksa dan memutus perkara pada tingkat pertama, ditambah dengan pemeriksaan tambahan apabila hakim berpendapat ada hal-hal yang memerlukan kejelasan atau untuk menambah kesempurnaan pembuktian. Tinjauan cita hukum terhadap penanganan sengketa ekonomi syariah di Pengadilan Tinggi Agama Semarang di antaranya: ditinjau dari cita hukum keadilan, hakim dalam mewujudkan cita hukum keadilan masih terkendala dengan ketentuan yang samar dalam peraturan perundang-undangan yang mengatur tentang bagaimana tata cara pemeriksaan sengketa ekonomi syariah di tingkat banding, yang mana hal ini menjadikan hakim tidak dapat mewujudkan keadilan yang diinginkan. Ditinjau dari cita kepastian hukum, kendala dalam mewujudkan cita hukum ini adalah tidak adanya ketentuan khusus yang mengatur tentang hukum acara perdata (tata cara pemeriksaan perkara) khususnya sengketa ekonomi syariah pada peradilan tingkat banding, ditambah lagi terdapat beberapa yurisprudensi Mahkamah Agung yang saling bertolak belakang/bertentangan. Sedangkan ditinjau dari cita hukum kemanfaatan, sebagian telah memenuhi cita hukum ini karena telah sesuai dengan ketentuan yang mengatur tentang biaya penanganan perkara dan jangka waktu penanganan perkara.